Land-sharing logging is more profitable than land sparing in the Brazilian Amazon. (14th October 2021) - Bousfield, Christopher G; Massam, Mike R; Acosta, Ileana A; Peres, Carlos A; Edwards, David P
Abstract: Selective logging is pervasive across the tropics and a key driver of forest degradation. Two competing harvest management strategies have been proposed: Land sharing via low-intensity logging throughout a concession; and high-intensity land-sparing logging across a smaller area, protecting part of the concession as primary forest. Empirical research points to land sparing being more optimal for maintaining biodiversity and carbon, especially under secure land tenure, but a key question for forest-based economies is how each strategy affects the profitability of logging. We combine detailed financial data with harvest simulations to assess the profitability of land-sharing and land-sparing logging in the Brazilian Amazon. Under business-as-usual, land-sharing is significantly more profitable than land-sparing logging, whether sparing is conducted in a single block or targeting the highest-density timber stocks, highlighting a conflict between economic and conservation priorities. Land-sharing logging is also more profitable than hybrid strategies whereby a mix of land-sharing and land-sparing logging is employed. Conservation-based restrictions that apply quotas on species in different size classes reduces the opportunity cost of land sparing, but even under tight restrictions land sharing remains more profitable and land sparing often returns a loss. Additional financial incentives, including timber certification schemes and carbon-based payment for ecosystem services, are needed to bridge the opportunity cost of land-sparing logging and minimise ecological damage to tropical rainforests.